Effectiveness of Mulligan's Movement with Mobilization and Muscle Energy Technique on Pain, Functional Status, and Depression in Students with Sacro Iliac Joint Dysfunction - Kumar, S. Siva; Mohanan, Kamalakannan; AP, Kalpana; Jayabalan, Parkash; Rajaram, Gowthan (Journal of Liaquat University of Medical & Health Sciences, 2023)
Objective: The study aims to identify the effectiveness of Mulligan's movement with mobilization and Muscle energy techniques on pain and functional disability in students with Sacro Iliac joint dysfunction. Methodology: This randomized control trial was conducted on college students with sacroiliac joint dysfunction recruited from KMCH Institute of paramedical sciences, Coimbatore, Tamil Nadu, India, from August 2019 to July 2020. Group A included 16 subjects and Group B with 15 subjects. The subjects who fall into the inclusion criteria were included, and subjects who are willing to participate in the study were included in this study. Neurological signs, Radiating pain below the knee, recent surgery & fracture around the hip, and hypermobile joint were excluded. Group A received Mulligan's mobilization and core stability exercise; Group B received muscle energy technique with core stability exercise. Outcome Measures: Pain and functional disability were measured by the modified Oswestry disability index; Kinesiophobia was by the Tampa scale. Results: The level of significance was 0.05. The mean values of the post-test show marked improvement between the groups, with a p-value of 2.69 for functional disability and a p-value of 0.45 for pain. Significant progress was observed in participants who received Mulligan's movement with mobilization. Statistical calculation was done with the help of SPSS version 18. Conclusion: Mulligan mobilization is more effective than the muscle energy technique in managing sacroiliac joint dysfunction.